Effect of Sequential Intrastromal Corneal Ring Segment Implantation and Corneal Collagen Crosslinking in Corneal Ectasia - Kim, Chung Young (Korean J Ophthalmol, 2019)
PURPOSE: To assess the clinical efficacy of sequential intrastromal corneal ring segment (ICRS) implantation and corneal crosslinking (CXL) in corneal ectasia. METHODS: This retrospective case series included eight eyes in which both ICRS implantation and CXL had been performed. CXL was performed within 1 month after ICRS implantation. The clinical outcomes (visual acuity, refractive errors, keratometry, and topographic indices) of these patients were compared with those of patients who had undergone only ICRS implantation (eight eyes) or CXL (20 eyes). RESULTS: Greater improvement in uncorrected visual acuity was observed in the ICRS + CXL group than in the ICRS or CXL alone groups at both 6 (p = 0.008) and 12 months (p = 0.028). Refractive errors of sphere and spherical equivalent were significantly reduced in both the ICRS (p = 0.002 at 6 months, p = 0.004 at 12 months) and ICRS + CXL groups (p < 0.001 at both 6 and 12 months). Keratometric values including the maximum, minimum, and average were significantly reduced in all 3 groups at postoperative 6 and 12 months; however, the greatest reductions were observed in the ICRS + CXL group (all p < 0.001). CONCLUSIONS: ICRS implantation followed by CXL within 1 month seems to be effective, and may be superior to ICRS or CXL alone in improving visual acuity and reducing refractive errors and keratometric values.